2018
DOI: 10.1002/ente.201800352
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable Energy System Utilizing High‐Voltage‐Stable and Energy‐dense Supercapacitors Based on Porous Fe2O3@Graphene Electrode in Ionic Liquid Electrolyte

Abstract: Energy‐dense supercapacitors (SCs) based on metal oxides@graphene electrode and ionic liquid (IL) electrolyte hold great promise in sustainable energy system. However, these types of SCs suffer from poor cycling stability, especially at high working voltage. Herein, a porous ferric oxide/graphene (P−Fe2O3/G) electrode has been developed, in which Fe2O3 nanoparticles exhibit abundant and suitable mesoporous channels. This structure ensures the high ionic diffusion kinetics of the IL ions during the repeated cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 77 publications
1
4
0
Order By: Relevance
“…In this context, we tried to understand the possible pseudocapacitive mechanism of the CC-LDH with [EMIM]­[BF 4 ] IL electrolyte based on our characterization and previous studies. The observed high capacitance of the present cell is believed to be because of the EMIM + cation in [EMIM]­[BF 4 ] IL electrolyte and the high ionic liquid ion density onto the electrode surface as per Kornyshev theory as discussed for electrode materials such as Fe 2 O 3 , FeOOH, etc. , In these reports and in similar other materials, it was observed that the electrostatic interaction between a charged surface electrode forms a dense grim layer and loose diffuse layer because of large size of EMIM + . It is less mobile due to its large size, and in the present case, it overlaps with the electron density cloud from the OH – of LDH and finally gets adsorbed on the surface of the electrode .…”
Section: Resultssupporting
confidence: 50%
See 2 more Smart Citations
“…In this context, we tried to understand the possible pseudocapacitive mechanism of the CC-LDH with [EMIM]­[BF 4 ] IL electrolyte based on our characterization and previous studies. The observed high capacitance of the present cell is believed to be because of the EMIM + cation in [EMIM]­[BF 4 ] IL electrolyte and the high ionic liquid ion density onto the electrode surface as per Kornyshev theory as discussed for electrode materials such as Fe 2 O 3 , FeOOH, etc. , In these reports and in similar other materials, it was observed that the electrostatic interaction between a charged surface electrode forms a dense grim layer and loose diffuse layer because of large size of EMIM + . It is less mobile due to its large size, and in the present case, it overlaps with the electron density cloud from the OH – of LDH and finally gets adsorbed on the surface of the electrode .…”
Section: Resultssupporting
confidence: 50%
“…Electrochemical charge storage characteristics of the CuCo-LDH material were further studied in a flexible cell using KOH as the electrolyte as described in the Experimental Section. The measured CV and GCD graphs, as shown in Figure S15 53,54 In these reports and in similar other materials, it was observed that the electrostatic interaction between a charged surface electrode forms a dense grim layer and loose diffuse layer because of large size of EMIM + . It is less mobile due to its large size, and in the present case, it overlaps with the electron density cloud from the OH − of LDH and finally gets adsorbed on the surface of the electrode.…”
Section: ■ Results and Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…The Raman spectra of Cu 9 S 5 /Fe 2 O 3 , Cu 9 S 5 and Fe 2 O 3 are displayed in Figure b. The peaks of Cu 9 S 5 /Fe 2 O 3 at 215 cm –1 correspond to the A 1g mode, and 281, 396, and 576 cm –1 correspond to the E g mode of the vibrations of Fe 2 O 3 . ,,, The peak at 482 cm –1 matches to Fe 2 O 3 and S–S stretching mode of Cu 9 S 5 . It is worth noting that the peak of pure Fe 2 O 3 shifts from 491 cm –1 to around 482 cm –1 of Cu 9 S 5 /Fe 2 O 3 , and the peak of pure Cu 9 S 5 shifts from 471 to 482 cm –1 of Cu 9 S 5 /Fe 2 O 3 .…”
Section: Results and Discussionmentioning
confidence: 65%
“…Transition-metal oxides are being well studied for high-quality devices because of their low price and low toxicity. ,− For example, a single-crystal Co 3 O 4 nanowire array on nickel foam had a specific capacitance of 754 F/g at 2 A/g . A network of MnO 2 –ERGO exhibits an excellent capacitance of 422.5 F/g at 1 A/g .…”
Section: Introductionmentioning
confidence: 99%